Practical Importance of Money-Credit Concepts - Mukhabbat Volnazarovna Imamova (Research Parks Publishers, 2021)
Improving monetary policy necessitates the study of the rules of leading monetary concepts and the formation of scientific and practical conclusions and recommendations that serve to justify their practical significance. The article examines the provisions of the leading monetary concepts and substantiates their use in improving the monetary policy of the Central Bank of the Republic of Uzbekistan.